Systematic theology ; v. 2, pts 5-7 - Chafer, Lewis Sperry, 1871-1952; Walvoord, John Flipse, 1910-; Campbell, Donald K.; Zuck, Roy B. (Wheaton, IL Victor, 1988)
Contents : v. 2 : pt 5: Soteriology; pt 6: Ecclesiology; pt 7: Eschatology. Includes bibliographical references and indexes.
Originally published, 1947, in eight volumes.
Keywords: Theology, doctrinal